2017: La Navidad de la rata - Calviño, Frank (Cambio Universitario, 2018)
Testimonial report of two children living in the Petare neighborhood of Caracas, Venezuela. They narrate that the main protein support of them and their families is the consumption of rats. The testimony is one of the hundreds that describe the situation of hunger and insecurity that exists in a country that until a few years ago enjoyed the highest GDP in Latin America and after the coming to power of Hugo Chávez Frías began its collapse, a situation that he sharpened his successor Nicolás Maduro Reportaje testimonial de dos niños que viven en el barrio Petare de Caracas, Venezuela. Narran que el principal sustento proteico de ellos y sus familias es el consumo de ratas. El testimonio es uno de los cientos que describen la situación de hambre e inseguridad que se vive en un país que hasta hace unos años disfrutó del mayor PIB de América Latina y luego de la llegada al poder de Hugo Chávez Frías comenzó su desplome, situación que agudizó su sucesor Nicolás Maduro.